Zydzi w Warszawie : zycie codzienne, wydarzenia, ludzie - Fuks, Marian (Poznan/Daszewice : Sorus, 1992)
An history of Jews and their life in Warsaw from earliest times to the present.
Includes bibliographical references (p. [372]-376) and index.
Keywords: Jews -- Poland -- Warsaw -- History; Warsaw (Poland) -- Ethnic relations